Reframing Conceptual Mastery in Financial Education: Digital STAD and Cognitive Engagement - Putu Arya Dharmayasa; García Fallas (Universitas Negeri Semarang, 2026)
Despite the expanding adoption of active and technology-mediated learning in economics education, robust empirical evidence on how digitally supported cooperative designs enhance conceptual mastery remains limited, particularly in teacher-education settings. This study investigates the pedagogical and cognitive effects of integrating the Student Teams Achievement Division (STAD) model with digital media on students’ understanding of money and financial institutions. Using a classroom-based quasi-experimental approach across iterative instructional cycles, data were obtained from structured observations of cognitive engagement and standardized assessments administered to undergraduate economics education students. The results indicate consistent gains in active learning participation and conceptual comprehension, reflected in progressively higher post-intervention scores. These findings suggest that digitally mediated cooperative learning can strengthen engagement and promote deeper conceptual processing. However, the study is constrained by its single-institution context, modest sample size, and quasi-experimental design, which limit causal generalization. The study extends cooperative learning into digital pedagogical environments and offers cautious implications for redesigning concept-focused instruction in higher education economics.